DETERMINAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA (BEI) - Izzatu Mukhlishoti; Syaiful Syaiful (PROCEEDING UMSURABAYA, 2022)
Corporate Social Responsibility (CSR) disclosure activities carried out by companies, especially companies in the mining sector, are still not optimal. This study aims to see what factors can affect the implementation of the company's CSR disclosures. Sampling using purposive sampling method with 70 research data. This study uses multiple linear regression analysis test. The results showed that the variables of profitability, firm size and growth had an effect on the disclosure of corporate social responsibility, but for corporate growth it was negatively related to the disclosure of corporate social responsibility. Further research is expected to use companies in other sectors with a longer period and it is suggested to add research variables that can affect the company's CSR disclosure.Keywords: Company Growth; Company Size; Corporate Social Responsibility (CSR) Disclosure; Profitability.